The diverse roles of miRNAs in HIV pathogenesis: Current understanding and future perspectives - Rashid, Farooq; Zaongo, Silvere D.; Song, Fangzhou; Chen, Yaokai (Frontiers in Immunology, 2023)
Despite noteworthy progress made in the management and treatment of HIV/AIDS-related disease, including the introduction of the now almost ubiquitous HAART, there remains much to understand with respect to HIV infection. Although some roles that miRNAs play in some diseases have become more obvious of late, the roles of miRNAs in the context of HIV pathogenesis have not, as yet, been elucidated, and require further investigations. miRNAs can either be beneficial or harmful to the host, depending upon the genes they target. Some miRNAs target the 3′ UTR of viral mRNAs to accomplish restriction of viral infection. However, upon HIV-1 infection, there are several dysregulated host miRNAs which target their respective host factors to either facilitate or abrogate viral infection. In this review, we discuss the miRNAs which play roles in various aspects of viral pathogenesis. We describe in detail the various mechanisms thereby miRNAs either directly or indirectly regulate HIV-1 infection. Moreover, the predictive roles of miRNAs in various aspects of the HIV viral life cycle are also discussed. Contemporary antiretroviral therapeutic drugs have received much attention recently, due to their success in the treatment of HIV/AIDS; therefore, miRNA involvement in various aspects of antiretroviral therapeutics are also elaborated upon herein. The therapeutic potential of miRNAs are discussed, and we also propose herein that the therapeutic potential of one specific miRNA, miR-34a, warrants further exploration, as this miRNA is known to target three host proteins to promote HIV-1 pathogenesis. Finally, future perspectives and some controversy around the expression of miRNAs by HIV-1 are also discussed.